Optimization of 2-(1H-imidazo-2-yl)piperazines series of Trypanosoma brucei growth inhibitors as potential treatment for the second stage of HAT. Issue 12 (15th June 2020) - Ciammaichella, Alina; Ferrigno, Federica; Basta, Andreina; D'Amico, Melania; Biancofiore, Ilaria; Nardi, Valentina; Ponzi, Simona; Graziani, Rita; Gennari, Nadia; Vittoria Orsale, Maria; Fini, Ivan; Paonessa, Giacomo; et al.
Graphical abstract: Abstract: A previous publication from our laboratory reported the identification of a new class of 2-(1 H -imidazo-2-yl)piperazines as potent T. brucei growth inhibitors as potential treatment for Human African Trypanosomiasis (HAT). This work describes the structure–activity relationship (SAR) around the hit compound 1, which led to the identification of the optimized compound 18, a single digit nanomolar inhibitor (EC50 7 nM), not cytotoxic and with optimal in vivo profile that made it a suitable candidate for efficacy studies in a mouse model mimicking the second stage of disease.